Biogenic Selenium Nanoparticles Synthesized with Alginate Oligosaccharides Alleviate Heat Stress-Induced Oxidative Damage to Organs in Broilers through Activating Nrf2-Mediated Anti-Oxidation and Anti-Ferroptosis Pathways - Xue-Qing Ye; Yan-Ru Zhu; Yu-Ying Yang; Sheng-Jian Qiu; Wen-Chao Liu (MDPI AG, 2023)
Selenium (Se) is an essential trace element for maintaining health due to its ideal antioxidant properties. We previously prepared a new type of biogenic selenium nanoparticles based on alginate oligosaccharides (SeNPs-AOS), and this study aimed to investigate the protective effects of SeNPs-AOS (Se particle size = 80 nm, Se content = 8%) on organ health in broilers challenged with HS. A total of 192 21-day-old Arbor Acres broilers were randomly divided into four groups according to a 2 × 2 experimental design, including a thermoneutral zone group (TN, raised under 23 ± 1.5 °C); TN + SeNPs-AOS group (TN group supplemented 5 mg/kg SeNPS-AOS); HS group (HS, raised under 33 ± 2 °C for 10 h/day); and HS + SeNPs-AOS group (HS group supplemented 5 mg/kg SeNPS-AOS). There were six replicates in each group (eight broilers per replicate). The results showed that SeNPs-AOS improved the splenic histomorphology, enhanced the activity of catalase (CAT) and glutathione peroxidase (GSH-Px) of the spleen, as well as upregulating the splenic mRNA expression of antioxidant-related genes in broilers under HS. In addition, SeNPs-AOS reversed the pathological changes in bursa caused by HS increased the activity of GST, GSH-Px, and CAT and upregulated the mRNA expression of Nrf2 and antioxidant-related genes in the bursa of heat-stressed broilers. In addition, dietary SeNPs-AOS improved the hepatic damage, increased the activity of GSH-Px in the liver, and upregulated the mRNA expression of antioxidant-related genes while downregulating the Keap1 gene expression of the liver in broilers during HS. Moreover, dietary SeNPs-AOS upregulated the anti-ferroptosis-related genes expression of liver in broilers under HS. In conclusion, dietary SeNPs-AOS could relieve HS-induced oxidative damage to the spleen, bursa of Fabricius and liver in broilers by upregulating the Nrf2-mediated antioxidant gene expression and SeNPs-AOS could also upregulate the expression of hepatic Nrf2-related anti-ferroptosis genes in heat-stressed broilers. These findings are beneficial for the development of new nano-antioxidants in broilers.